Alcohol consumption and persistent infection of high-risk human papillomavirus - OH, H. Y.; KIM, M. K.; SEO, S.; LEE, D. O.; CHUNG, Y. K.; LIM, M. C.; KIM, J.; LEE, C. W.; PARK, S. (Epidemiology and infection, 2015)
Alcohol consumption is a possible co-factor of high-risk human papillomavirus (HR-HPV) persistence, a major step in cervical carcinogenesis, but the association between alcohol and continuous HPV infection remains unclear. This prospective study identified the association between alcohol consumption and HR-HPV persistence. Overall, 9230 women who underwent screening during 2002–2011 at the National Cancer Center, Korea were analysed in multivariate logistic regression. Current drinkers [odds ratio (OR) 2·49, 95% confidence interval (CI) 1·32–4·71] and drinkers for ⩾5 years (OR 2·33, 95% CI 1·17–4·63) had a higher risk of 2-year HR-HPV persistence (HPV positivity for 3 consecutive years) than non-drinkers and drinkers for <5 years, respectively (vs. HPV negativity for 3 consecutive years). A high drinking frequency (⩾twice/week) and a high beer intake (⩾3 glasses/occasion) had higher risks of 1-year (OR 1·80, 95% CI 1·01–3·36) HPV positivity for 2 consecutive years) and 2-year HR-HPV persistence (OR 3·62, 95% CI 1·35–9·75) than non-drinkers. Of the HPV-positive subjects enrolled, drinking habit (OR 2·68, 95% CI 1·10–6·51) and high consumption of beer or soju (⩾2 glasses/occasion; OR 2·90, 95% CI 1·06–7·98) increased the risk of 2-year consecutive or alternate HR-HPV positivity (vs. consecutive HPV negativity). These findings suggest that alcohol consumption might increase the risk of cervical HR-HPV persistence in Korean women.